A folded dual‐mode bandpass filter with circular waveguide. Issue 4 (28th November 2017) - Wu, Zhi‐Hang; Zhang, Ke‐Qing; Hao, Tian‐Qi; Wang, Zheng‐bin; Huang, Bo
Abstract: In this article, a folded circular waveguide dual‐mode filter without tuning screws is designed for the fifth‐generation (5G) mobile communication system. The folded filter is composed of two stacked circular cavities operated at 3.5 GHz. Each cavity has two resonant modes, which can generate and control two transmission zeroes at specific frequencies. Through a coupling iris, the two single‐cavity filters are connected together, and can control four poles, which helps to expand the 3dB fractional bandwidth to 11.4%. The measured insertion losses are around 0.5 dB in the passband (from 3.4–3.6 GHz). The experiment results show an excellent agreement with the simulation results. Such folded filters have the advantages of very low insertion loss, compact size, high frequency selectivity, and low cost.